Efficacy and safety of hydroxychloroquine in the treatment of type 2 diabetes mellitus: a double blind, randomized comparison with pioglitazone. (July 2014) - Pareek, Anil; Chandurkar, Nitin; Thomas, Nihal; Viswanathan, Vijay; Deshpande, Alaka; Gupta, O.P.; Shah, Asha; Kakrani, Arjun; Bhandari, Sudhir; Thulasidharan, N.K.; Saboo, Banshi; Devaramani, Shashidhar; et al.
Abstract Objective: To compare efficacy and safety of hydroxychloroquine with pioglitazone in type 2 diabetes mellitus (T2DM). Research design and methods: This double-blind study randomized 267 uncontrolled type 2 diabetes patients (HbA1c ≥7.5% and ≤11.5%), post 3 months' treatment with glimepiride/gliclazide and metformin, to additionally receive hydroxychloroquine 400 mg/day (n = 135) or pioglitazone 15 mg/day (n = 132) for 24 weeks. Efficacy was assessed by changes in HbA1c, fasting (FBG) and post-prandial (PPG) blood glucose at Week 12 and Week 24. Results: At Week 12 and Week 24, HbA1c, FBG and PPG significantly reduced from baseline in both groups. Mean reduction in glycemic parameters at Week 12 (HbA1c: −0.56% vs −0.72%, p = 0.394; FBG: −0.99 mmol/L vs −1.05 mmol/L, p = 0.878; PPG: −1.93 mmol/L vs −1.52 mmol/L, p = 0.423) and Week 24 (HbA1c: −0.87% vs −0.90%, p = 0.909; FBG: −0.79 mmol/L vs −1.02 mmol/L, p = 0.648; PPG: −1.77 mmol/L vs −1.36 mmol/L, p = 0.415) was not significantly different between the hydroxychloroquine and pioglitazone groups. Change in total cholesterol (TC) and LDL-C was significant in favor of hydroxychloroquine (TC: −0.37 mmol/L vs 0.03 mmol/L, p = 0.002; LDL-C: −0.23 mmol/L vs 0.09 mmol/L, p = 0.003). Triglycerides significantly reduced in both groups at Week 24. Mean HDL-C remained unchanged. Study treatments were well tolerated. Conclusion: With favorable effects on glycemic parameters and lipids, hydroxychloroquine may emerge as well tolerated therapeutic option for T2DM. Limitations: The sample size for this study was small. However, based on the encouraging results of this proof-of-concept study, longer duration studies in larger population can be conducted to further confirm these findings. Trial registration details: Clinical Trial Registry–India URL: http://ctri.nic.in, Registration Number: CTRI/2009/091/001036.